Hardness and corrosion behaviour of anodised Al-Si produced by rheocasting. (5th July 2019) - Zhu, Baiwei; Zanella, Caterina
Abstract: The anodised layer of Al-Si alloys produced by rheocasting was studied and compared to anodised traditional liquid casting in this paper. The anodising was performed in 1.0 M H2 SO4 solution at room temperature on the as-cast substrates, and anodising voltage and time were optimised as process parameters. This study focuses on understanding the effect of the surface liquid segregation (SLS) layer by rheocasting on the hardness and corrosion protection of the oxide layer. The hardness depends on the anodising parameters and varies along the oxide thickness. The corrosion protection given by the oxide layer was evaluated by electrochemical impedance spectroscopy (EIS) in 3 wt-% NaCl solution, and the results revealed that the longitudinal macrosegregation influences the corrosion protection, with the near-to-vent region showing lower corrosion protection due to a higher eutectic fraction. A comparison between liquid and rheocast samples indicated that the presence of SLS layer by the transverse macrosegregation does not have a significant impact on the corrosion resistance of the oxide layer. Moreover, it was found that an increase of the oxide layer thickness by longer anodising time or higher applied voltage decreases both the hardness and corrosion resistance of the oxide layer. Graphical abstract: Unlabelled Image Highlights: Fe-intermetallics dissolved partly during anodising, leaving vacancies as defects remain in the oxide layer. The longitudinal macrosegregation influences the corrosion protection of the oxide layer but does not affect its hardness. The surface liquid segregation (SLS) layer on rheocasting behaves as a skin effect on the as-cast surface. Higher oxide thickness decreases the hardness and corrosion resistance of the oxide layer.